Penerapan Model Pembelajaran Problem Based Learning Untuk Meningkatkan Hasil Belajar Geografi Peserta Didik Kelas X IIS 1 SMA Negeri 9 Sinjai - Irmawati, Irmawati (LaGeografia, 2019)
This research aims to improve the learning results of geography materials lithosphere dynamics and their impact on life through the application of the model of learning problem based learning. Data collection was done through the test results of the study. Using quantitative analysis. The minimum completeness criterion is 70. The results of the analysis show that the learning outcomes of students have increased seen from the average value of learning outcomes in the first cycle, namely 70.00 with the percentage of classical learning completeness which is 51.72% increased in the second cycle with an average value of 85.34 with the percentage of mastery learning in classical is 100%. The conclusion of this research is the application of the model of learning problem based learning can improve the results of studying the geography of the learners.